2005
DOI: 10.1177/000331970505600107
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Genotype in Dyslipidemic Patients and Response of Blood Lipids and Inflammatory Markers to Alpha-Linolenic Acid

Abstract: The objective of this study was to determine the effect of alpha-linolenic acid (ALA) supplementation on blood lipids and inflammatory markers, in relation to apolipoprotein (apo) E genotype. The diets of 50 dyslipidemic male patients were supplemented with 15 mL of flaxseed oil per day for 12 weeks. Retrospectively, 3 apo E genotype variants were found (epsilon2/epsilon3, n=7; epsilon3/epsilon3, n=33; epsilon3/epsilon4, n=10). No significant differences were found among apo E genotypes in any variables at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 58 publications
4
30
1
Order By: Relevance
“…Recently, alpha-linolenic acid has been advocated as well, as an antagonist for groups with increased cardiovascular risk. 9 No study in obese populations has been found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, alpha-linolenic acid has been advocated as well, as an antagonist for groups with increased cardiovascular risk. 9 No study in obese populations has been found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Moreover, some other gene polymorphisms were associated with circulating levels of the hs-CRP, the most studied being the common polymorphisms of the apolipoprotein E gene (APOE) (e2, e3, e4) for which an association was confirmed by many authors in adults and elderly. 12,[18][19][20][21][22][23][24] However, no data exist either about APOE genotype-hs-CRP concentration association in children or about effect of these polymorphisms in combination with estimate of heritability component. 12 Thus, in the present analysis, we aimed at reporting on (i) the association between the APOE gene alleles with the serum hs-CRP concentration in adults and also in children, (ii) the familial aggregation of the serum hs-CRP concentration on a sample of French nuclear families and on (iii) the variance-component genetic linkage of this inflammatory factor with the alleles of the APOE gene.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, increased intake of ALA reduced CRP [29,31,35], IL-6 [31], and sVCAM-1 levels [29], but this did not occur in all studies [30]. Increased intake of ALA reduced sICAM-1 and E-selectin levels in some studies [29] but not in others [35].…”
Section: Alamentioning
confidence: 91%
“…In some studies, ALA reduced TC, LDL-C, TG [29], and lipoprotein(a) levels [30]. However, in other studies, ALA had no effect on these variables [30,31]. Unfavorable actions, including an increase in TC [32] and TG levels, were also reported [33].…”
Section: Alamentioning
confidence: 99%